Sintesis dan Karakterisasi Silika Berpori dari Natrium Silikat dan Surfaktan Gelatin Kulit Ikan Gabus Channa Striata - Erpina, Erpina; Aini, Syamsi; Khair, Miftahul; Ningsih, Sherly Kasuma Warda (Periodic, 2024)
Porous silica is a solid silica material for chemical sensors. Porous materials can be divided into 3 categories based on pore size, namely microporous material with pore size less than 2 nm, mesoporous pore between 2 to 50 nm, and macropores with a pore size of more than 50 nm.This research was conducted to synthesize porous silica using sodium silicate with variations of snakehead fish skin gelatin (3% and 4%) using the sol-gel method. Snakehead fish skin gelatin was characterized using FTIR and porous silica was characterized using XRD and SEM. The results of the FTIR test on snakehead fish skin gelatin show that there are indicates that snakehead fish skin gelatin contains amide, carboxyl and carbonyl groups which can interact with sodium silicate. Characterization of porous silica using XRD shows that the resulting porous silica is crystalline. Meanwhile, SEM characterization shows a regular morphology at 4% which has the highest crystallinity and branched tube morphology.